International organization: A dictionary and directory - Schiavone, Giuseppe (St. Martin's, 1993)
This book consists of alphabetically-arranged entries for over 100 organizations - from the United Nations to specialized agencies and regional and subregional bodies - including intergovernmental fora such as the Conference and Security and Co-operation in Europe (CSCE), the North Atlantic Co-operation Council (NACC), and the Asia Pacific Economic Co-operation (APEC). Each entry describes the objectives, functions, powers and activities, providing an assessment of the role of the organizations concerned. Specific data regarding addresses, principal officers, main peridic publications and a short list of works of reference are also supplied. At the end of the dictionary section, a separate listing provides essential information for a further 100 organizations with laegely technical and administrative tasks. Access to all entries is expedited by an index of acronyms and full names. Detailed membership charts, tables of foundation dates and classified index complete the book